TP2-3 Long-term survival and five year hospital resource usage following traumatic brain injury in scotland from 1997–2015: a population-based retrospective cohort study. Issue 3 (14th February 2019) - Loan, JJM; Scott, NW; Jansen, JO
Abstract : Aim: To determine if survival and hospital resource usage differ following traumatic brain injury (TBI) compared with head injury without neurological injury(HI). Methods: This retrospective population-based cohort study included all 25 319 patients admitted to a Scottish NHS hospital from 1997–2015 with TBI. Participants were identified using previously validated ICD-10 based definitions. For comparison, all 194 049 HI cases were identified. Our main outcome measures were hazards of all-cause mortality after TBI, compared with HI, over 18 years follow-up period; and odds of mortality at one month post-injury. Number of days spent as inpatients and number of outpatient attendances per surviving month post-injury were used as measures of resource utilisation. Results: The adjusted odds ratio for mortality in the first month post-injury for TBI was 7.12 (95% confidence interval [CI] 6.73–7.52; p<0.001). For the remaining 18 year study period, the hazards of morality after TBI were 0.93 (CI 0.90–0.96; p<0.001). TBI was associated with 2.15 (CI 2.10–2.20; p<0.001) more days spent as inpatient and 1.09 times more outpatient attendances (CI 1.07–1.11; p<0.001) than HI. Conclusions: Although initial mortality following TBI is high, survivors of the first month can achieve comparable long-term survival to HI. However this is associated with increased utilisation of hospital services in the TBI group.